Wedding Preparedness Of Prspective Bride and Groom - Eprila; Yunike (International Journal Scientific and Professional (IJ-ChiProf), 2022)
Committed to entering marriage requires an understanding of the readiness to carry out a role in the family to be committed for life to form a happy family. The complex psychological challenges and problems associated with failure to properly prepare for marriage will result in misery and threaten the quality of life of family members. Research that explores the preparation of the bride and groom in entering the marriage gate is still very limited, even though this topic has implications for the achievement of family happiness. The purpose of this study was to explore the readiness of the bride and groom in undergoing marital status. This qualitative research explores the facts in the field to describe and analyze the phenomenon of the wedding preparation of the bride and groom. Data collection was carried out through in-depth interviews with six pairs of prospective brides and grooms who were going to get married in the same year. Determination of participants is adjusted based on the inclusion criteria of research participants and the number is determined based on the results of data saturation. The theme of this research is the legacy of parental experience, ignoring the most important marriage, financial and work planning and the lack of anticipation of physical and psychological changes. The results of the study concluded that the preparation of the bride and groom that is not comprehensive has the opportunity to lead to marriage failure. Explanation of wedding preparation through the use of technology is suggested as an implementation of increasing literacy of the bride and groom, in collaboration with the Office of Religious Affairs which legalizes marriage.